A faked prolongation of an endurance target time does not affect muscle fatigue but increases perceived exertion - Herzberg, Max; Rosendahl, Jenny; Mader, Lena; Anders, Christoph (Frontiers in Psychology, 2025)
ObjectiveWhile psychological factors are known to influence physical performance, responses to unexpectedly extended endurance tasks remain unclear.MethodsIn a crossover-randomized study, 37 participants performed an isometric endurance task twice, with a 14-day interval, compensating for 50% of upper body weight for 10 min. Muscular fatigue was measured via EMG of the back muscles, and perceived exertion (RPE; Borg scale 6–20) was recorded every minute (Real). In the experimental condition (Fake), RPE was recorded every 50 s without participants’ awareness. After the tenth query, participants were told a technical error occurred and were asked to continue for two additional minutes with two extra RPE queries. Participants were grouped by RPE and Fatigue Index (FI) into “good-end” and “bad-end” groups. FI and RPE were compared between Real and Fake conditions.ResultsRPE-based grouping showed no significant FI differences. FI-based grouping revealed significantly higher RPE in the “good-end” group during the Fake condition (+0.9 at 540/550 s; +1.0 at 600 s). No significant differences were found in the “bad-end” group.ConclusionExtending a task beyond its expected endpoint increases perceived exertion, which may lead to task termination despite unchanged muscular fatigue.